Karakteristik bakteri asam laktat dan perubahan kimia pada fermentasi "bekasam" ikan mujair (Tilapia mossambica) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1997)
ABSTRACT This research aims was to characterize and test the antimicrobial activity of lactic acid bacteria isolated from bekasam (a fermented rice, salt and fish mixture). The changes of total protein, fat, titratable acidity, pH, water content, ash, starch, reducing sugar and total volatile bases (TVB) in bekasam during fermentation were also evaluated. Bekasam were made by spontaneous fermentation of salt, mu' air fish (Tilapia mossambica) and rice (0.2: 1: 1) mixture for 7 days. Result indicated that during fermentation period total mold increased from 3.9 x 104 cfu/gr to 3.2 x 105 cfu/ gr, total yeast increased from 2.3 x 105 cfu/gr to 5.2 x 107 cfu/gx and totalbacteria increased from 5.6 x 106 cfu/gr to 6.7 x 103 cf-u / e mold, yeast and bacteria other than lactic acid bacteria were not er identified. During 7 days fermentation of bekasam total lactic acid bacteria increased from 8.9 x 106 cfu /gr to 8.7 x 108 cfu/gr. Further identification based on morphological and biochemical properties indicated that Leuconostoc mesenteroides were isolated in the sample from day 1 to 7, Lactobacillus acidophilus from day 5 to 7, L.plantarum, L.fermentum from day 1, L.buchneri, L.reuteri from day 3, Pediococcus pentosaceus, L.iactis, L.coryniformis from day 5, whereas Streptococcus raffinolactis, L.clelbrueckii, L. halotolerans, L.bifermentans, L.tolerans, Pediococcus acidilactici, L.bulgaricus, Leu.dextranicum were isolated in the sample from day 7_ Antimicrobial activity of the isolated lactic acid bacteria against S.aureus occurred in Lactobacillus plantarum, Lfrrmentum, L.acidophilus and Pediococcus acidilactici. Statictical analysis based on 95% confidence interval showed that significant.chances of protein, fat, starch, total acid, pH and TVB were observed in bekasam during 7 days of fermentation. The value of protein decreased from 10.2% to 7.8%, fat decreased from 4.2% to 0.7%, starch decreased from 6.12% to 3.23%, total acidity increased from 0.2% to 0.55%, pH decreased from 5.22 to 3.68 and TVB increased from 0.12 % to 0.15 /o.